Evaluation of sex differences in dietary behaviours and their relationship with cardiovascular risk factors: a cross-sectional study of nationally representative surveys in seven low- and middle-income countries - McKenzie, Briar; Santos, Joseph Alvin; Geldsetzer, Pascal; Davies, Justine; Manne-Goehler, Jennifer; Gurung, Mongal Singh; Sturua, Lela; Gathecha, Gladwell; Aryal, Krishna K.; Tsabedze, Lindiwe; Andall-Brereton, Glennis; Bärnighausen, Till; et al. (Nutrition journal, 2020)
Cardiovascular diseases (CVD) are the leading causes of death for men and women in low-and-middle income countries (LMIC). The nutrition transition to diets high in salt, fat and sugar and low in fruit and vegetables, in parallel with increasing prevalence of diet-related CVD risk factors in LMICs, identifies the need for urgent action to reverse this trend. To aid identification of the most effective interventions it is crucial to understand whether there are sex differences in dietary behaviours related to CVD risk.